PENGARUHLPEMAHAMANHPERPAJAKANYDAN SANKSILPAJAK TERHADAPOKEPATUHANIWAJIBHPAJAKTUMKM KPPIPRATAMA BANDA ACEH - Ratna Juwita; Ratih Anggraini Siregar (Jurnal Widya, 2024)
Taxpayer complianceois taxpayeroactions to comply with tax regulations inlaccordance withiapplicable taxilaw. This researchoaims toiunderstand andlanalyze theleffect oflUnderstanding Taxation and TaxySanctions onlTaxpayer Complianceiat KPP Pratama Banda Aceh inz2018-2022. Dataicollection methodsiare usingiquestionnaires, interviewsland literatureistudy. Theidata used inithis research is primaryidata collectedithrough aiquestionnaire, surveyiand secondaryidata obtainedifrom KPP Pratama Banda Aceh, namelyidata for 2018-2022, namelyitheitotalinumberiof UMKM taxpayersiwho reportiSPT and UMKMitaxpayers whoido notireport SPT, whileitheisample in thisistudyiamounted to 50itaxpayers. Theiresults ofithe analysisishow thatiunderstanding has a significantlinfluence onitaxpayer complianceiand taxisanctions have a significantiinfluence on taxpayerlcompliance. Thisoresearch indicatesithat dimultaneouslyiunderstanding of taxationiand taxisanctions affectitaxpayer compliance. Theiimplication of thislresearch is thatlit is hopedlthat peoplelas personalltaxpayers andicorporate taxpayersican understandithe importance of paying taxesiand are ableito payitaxes inlorder to increaseltax revenues. In addition, so thatltaxpayers caniavoid taxisanctions thatlwill beiimposed ifltaxpayers violateitaxirules.